Active vs. passive recovery during high-intensity training influences hormonal response - Wahl, P.; Achtzehn, S.; Bloch, W.; Mester, J. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Recently, there have been numerous studies published in the area of high intensity training (HIT), showing that HIT is an effective and time saving method to improve endurance performance. However, until now, there have been no studies in the literature to examine the effects of active (A-) and passive (P-) recovery on the acute hormonal response. We hypothesized that A-recovery between high intensity intervals reduces the metabolic stimulus and therefore the hormonal response compared to P-recovery.